Розробка бізнес-плану вирощування цукрової кукурудзи для малих підприємств півдня України - Лисак, Оксана Іванівна; Тебенко, Віта Миколаївна; Завадських, Ганна Миколаївна; Lysak, Oksana; Tebenko, Vita; Zavadskykh, Hanna (Запоріжжя : 2022, 2022)
UA: Питання бізнес-планування в сільському господарстві завжди займали значне місце в наукових роботах вітчизняних та зарубіжних дослідників. Серед українських науковців значний вклад в проблеми бізнес-планування здійснили Ю. Е. Губені, І. І. Костецька [1], А. О. Гуторов [2], М. І. Кісіль, М. М. Кропивко [3], Т. В. Майорова [4] тощо. Серед зарубіжних досліджень роботи Дж. С. Мболі , Д. Таккера [10], Ф. А. Гоні [11], Б. Собіров [12] тощо. Проте, високо оцінюючи їх внесок, варто поглибити дослідження проблем бізнес-планування, в тому числі особливостей складання бізнес-планів для окремих продуктів з розробкою умов їх практичного втілення. EN: The article substantiates the idea of the project, provides general information about the project: types of activity, site and social significance; analysis of sweet corn production was carried out. The idea of the project is to increase the profitability of the entrepreneurial activity of the FOP "Marakhovskyi M.A." by growing and selling sweet corn. The object of the project is the process of growing sugar corn. A marketing plan (marketing goals, product promotion, sales channels, consumers, competitors, SWOT analysis matrix and price policy), organizational and production plans was drawn up. It was determined that the most attractive way to sell grown sweet corn for the Zaporizhzhia region would be freezing and selling fresh cobs. The sale of products is planned in Zaporizhzhia, Dnipropetrovsk, Kharkiv, as well as in wholesale lots to remote regions. To implement the business plan, investments in the amount of UAH 170,000 are required, and the amount of current costs for the production and sale of the warehouse is UAH 60,000. UAH annually. As a result of the conducted research, the total cost of the project was calculated; main economic indicators of the implementation of the investment project; the types of risks that can affect the project are identified and the measures to reduce their negative impact are given. The net modern value of the project for 3 years is UAH 234.4 thousand, the payback period of the investment composition is 1.1 years, the benefits of the project exceed its costs by 4 times. According to the obtained indicators, the project is attractive for implementation. The development scenarios are considered, taking into account the sensitivity to changes in the market. Under the conditions of implementation of a realistic scenario, the profitability of corn cultivation will be - 259%. When implementing an unfavorable - pessimistic scenario, corn production earns a profit, but the payback period for investments increases to 2 years.
Business plan development of growing sweet corn for small enterprises in southern Ukraine
Лисак О. І., Тебенко В. М., Завадських Г. М. Розробка бізнес-плану вирощування цукрової кукурудзи для малих підприємств півдня України. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. 2022. Вип. 12. том 3. C. 159-172.
Keywords: кукурудза цукрова; ринок овочевої продукції; інвестиційний проект; маркетинговий план; виробничий план; фінансові показники інвестиційного проекту; оцінка ризиків проекту; sweet corn; market of vegetable products; investment project; marketing plan; production plan; financial indicators of the investment project; project risk assessment